(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2018)
Herein, the authors report on skulls, mandibles and postcranial specimens of two species of Chinese Sivalhippus, S. ptychodus and S. platyodus. We frame our description and analyses within the context of newly described characters of the cheek teeth of Hippotherium from the Pannonian C of the Vienna Basin, the oldest and most primitive Old World hipparions. Our report includes original skull, mandibular and limited postcranial material of Sivalhippus ptychodus and skulls and dentitions of Sivalhippus platyodus from the Paleontological Museum of Uppsala (PMU, Uppsala, Sweden), the American Museum of Natural History (AMNH, New York, USA) and the Licent Collection in Tianjin Natural History Museum (Tianjin, China). The skull, maxillary and mandibular material we attribute to Sivalhippus ptychodus and Sivalhippus platyodus exhibit some primitive features for Old World hipparions and synapamorphies of the face and dentition that unite it with the Sivalhippus clade. Our analysis shows that S. ptychodus and S. platyodus differ significantly from the Cormohipparion occidentale – Hippotherium primigenium clade. Species belonging to the Sivalhippus clade are found in IndoPakistan (S. nagriensis, S. theobaldi, S. perimensis and S. anwari), Libya and Kenya (S. turkanensis) and Uganda (S. macrodon). We hypothesize that the Sivalhippus clade originated in South Asia where it is earliest represented by Sivalhipus nagriensis, ca. 10.4 Ma and underwent range extension into Africa and China circa 9-7 Ma.